AUTOMATION OF ITEMS ARRANGEMENT USING ROBOTIC ARM - Atmoko Nugroho; Gigih Budi Prastyo (JAICT, 2019)
In the industrial world, the process of arranging or moving item at the company still use human labor. This process requires a lot of manpower and time and labor costs. In today's, developing robotic technology is expected to be useful for all fields, one of them is in the industrial world in order to ease human work in doing their work in the industrial world. A robotic ARM can be driven automatically in a limited space and controlled by an Atmega328 microcontroller (Arduino UNO R3 DIP). A potentiometer is used as manual control of the mini servo motor and two buttons as a function of recording and moving automatically. This robot arm uses 4 mini servo motors as arm drive. The purpose of making this tool is expected to assist in solving a small part of the problems that exist in the world of industry.